2020
DOI: 10.5194/acp-20-12569-2020
|View full text |Cite
|
Sign up to set email alerts
|

A microphysics guide to cirrus – Part 2: Climatologies of clouds and humidity from observations

Abstract: Abstract. This study presents airborne in situ and satellite remote sensing climatologies of cirrus clouds and humidity. The climatologies serve as a guide to the properties of cirrus clouds, with the new in situ database providing detailed insights into boreal midlatitudes and the tropics, while the satellite-borne data set offers a global overview. To this end, an extensive, quality-checked data archive, the Cirrus Guide II in situ database, is created from airborne in situ measurements during 150 flights in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
206
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(231 citation statements)
references
References 93 publications
25
206
0
Order By: Relevance
“…Heterogeneity of microphysical properties encountered inside cirrus clouds can be explained by small-scale GWs (Jensen et al, 2013). The climatology from Krämer et al (2020) shows (in their Figure 8) that ice concentrations (for radius above 3 µm) in young cirrus are most frequently around 100 L −1 . Although cirrus with ice concentrations above 10,000 L −1 have already been observed (Krämer et al, 2009;Jensen et al, 2009;Krämer et al, 2020), only less than 10% of the observed TTL ice concentrations exceed 1,000 L −1 (Krämer et al, 2020).…”
Section: Microphysical Properties Of the Observed Ttl Cirrusmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneity of microphysical properties encountered inside cirrus clouds can be explained by small-scale GWs (Jensen et al, 2013). The climatology from Krämer et al (2020) shows (in their Figure 8) that ice concentrations (for radius above 3 µm) in young cirrus are most frequently around 100 L −1 . Although cirrus with ice concentrations above 10,000 L −1 have already been observed (Krämer et al, 2009;Jensen et al, 2009;Krämer et al, 2020), only less than 10% of the observed TTL ice concentrations exceed 1,000 L −1 (Krämer et al, 2020).…”
Section: Microphysical Properties Of the Observed Ttl Cirrusmentioning
confidence: 99%
“…However, Jensen et al (2016a) argued that the overall impact of the high-frequency waves is to increase ice concentrations produced by homogeneous freezing; the quenching of ice nucleation would only represent 11% of the events. In some infrequent cases, TTL cirrus have been observed with ice concentrations above several thousands per liter (Jensen et al, 2013;Krämer et al, 2020), in which case homogeneous nucleation is the only plausible explanation.…”
Section: Introductionmentioning
confidence: 99%
“…This allows for the measurement of air masses at an angle between 45 • and ≈ 132 • with respect to the flight direction. By constantly panning the instrument over the available angles, the same air masses are measured from multiple directions, which enables the tomographic reconstruction of three-dimensional structures (Ungermann et al, 2011;Krisch et al, 2017Krisch et al, , 2018. In addition to the IR instrument, there is also a standard camera with three channels (red/green/blue) operating in the visible range that observes a much wider field of view.…”
Section: Gloria and Irlsmentioning
confidence: 99%
“…The horizontal resolution is on the order of 30 km in the flight-track direction and 70 km orthogonal to that. Circular flight patterns, or, better, a backwards-viewing limb satellite, could further improve the horizontal resolution (Ungermann et al, 2011;Krisch et al, 2017).…”
Section: -D Retrievals Using Gloria Measurementsmentioning
confidence: 99%
“…Dolinar et al (2019) reported that single-layer ice clouds have a global occurrence frequency of about 18 %. Ice clouds are an important component of the planetary radiation budget in terms of magnitude; plus, they influence hydrological and climate sensitivities and affect surface climate (Runheng and Liou, 1985;Yang et al, 2015;Gultepe and Heymsfield, 2016;Lawson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%